2022
DOI: 10.7554/elife.76823
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-EM structure of the human somatostatin receptor 2 complex with its agonist somatostatin delineates the ligand-binding specificity

Abstract: Somatostatin is a peptide hormone that regulates endocrine systems by binding to G-protein-coupled somatostatin receptors. Somatostatin receptor 2 (SSTR2) is a human somatostatin receptor and is highly implicated in hormone disorders, cancers and neurological diseases. Here, we report the high resolution cryo-EM structure of full-length human SSTR2 bound to the agonist somatostatin (SST-14) in complex with inhibitory G (Gi) proteins. Our structural and mutagenesis analyses show that seven transmembrane helices… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Furthermore, the Lys residue in each ligand (K9 for SST14 and K5 for both OCT and CYN) stably interacts with D122 3.32 , Q126 3.36 and Y302 7.43 , as already reported in literature based on structural data 25 . Differently, we found that the Trp residue (W8 for SST14 and D W4 for both OCT and CYN) maintains the interaction with I177 4.60 , looses that with F208 5.38 , and gains an additional one, Q126 3.36 (for SST14 and OCT) or D122 3.32 (for CYN).…”
Section: Sstr2 Agonists and Antagonist Show Different Interaction Pat...supporting
confidence: 77%
See 1 more Smart Citation
“…Furthermore, the Lys residue in each ligand (K9 for SST14 and K5 for both OCT and CYN) stably interacts with D122 3.32 , Q126 3.36 and Y302 7.43 , as already reported in literature based on structural data 25 . Differently, we found that the Trp residue (W8 for SST14 and D W4 for both OCT and CYN) maintains the interaction with I177 4.60 , looses that with F208 5.38 , and gains an additional one, Q126 3.36 (for SST14 and OCT) or D122 3.32 (for CYN).…”
Section: Sstr2 Agonists and Antagonist Show Different Interaction Pat...supporting
confidence: 77%
“…Robertson and co-workers released the first cryo-EM structures of SSTR2 bound with SST14 and octreotide 24 . New structures soon followed, also in complex with other ligands 14,15,25,26 and one in the apo inactive form 27 (Table S1). An important feature of the SSTR2…”
mentioning
confidence: 99%
“…Interestingly, previous works reported the key role of Tyr205 5.35 and Ile195 in the interaction of SSTR2 with SST14 and octreotide (through F7 and F3, respectively), and it was also pointed out that these two residues can contribute to the selectivity of the different SSTR isoforms. 20 , 21 , 13 , 23 , 28 Furthermore, Phe294 7.35 and Ser279 6.58 (belonging to the hydrophobic sub-pocket constituted by TM6–7 and ECL3 13 ) seem to be involved in isoform selectivity as well, 23 and we found consistently their interaction with the disulfide bridge featured by all compounds (75/70% for 68 Ga-DOTATOC, 86/81% for 68 Ga-DOTATATE, 77/41% for 68 Ga-DOTANOC). Although the aforementioned interactions are conserved, we noticed some differences in the persistence of the DOTA-Tyr205 5.35 interaction.…”
Section: Resultsmentioning
confidence: 99%
“…The heterotrimeric mGαq iN /Gβ1γ2 was designed as previously described in mini-Gαq/Gβ1γ2 [ 20 ]. Single chain antibody scFv16 containing GP67 secretion signal sequence was also inserted into pFastBac1 vector [ 21 ].…”
Section: Methodsmentioning
confidence: 99%